Anomalous propagation conditions observed over a tropical station using high‐resolution GPS radiosonde observations. Issue 1 (1st March 2013) - Basha, Ghouse; Venkat Ratnam, M.; Manjula, G.; Chandra Sekhar, A. V.
<x xml:space="preserve">Abstract</x> A comprehensive study on the ducting conditions prevailing over the Indian tropical station of Gadanki (13.5°N, 79.2°E) is made using more than 5 years (April 2006 to September 2011) of high‐resolution GPS radiosonde observations. In the present study, the characteristics of ducts occurring over Gadanki were examined statistically using the modified refractivity. Strong diurnal and seasonal variation in the percentage occurrence of the ducts was found with the highest and lowest occurrences during winter and monsoon seasons, respectively. Duct strength is very strong during midnight to the morning hours than in the evening hours particularly during winter. The mean thickness of the duct and the duct strength were found to be the highest and the strongest in postmonsoon and winter seasons, whereas they are the lowest and the weakest in the monsoon season. Elevated ducts were found to be stronger than the surface and the surface‐based ducts. The characteristics of ducts during stable and unstable conditions were also investigated, and it was found that the duct altitude is higher during the stable conditions and is higher during premonsoon followed by postmonsoon, winter and minimum in the monsoon. The maximum wavelength being trapped was investigated, and it was found that wave trapping occurs for the radars with frequencies of 60 GHz and above.